Simultaneous‐count models to estimate abundance from counts of unmarked individuals with imperfect detection. Issue 3 (7th January 2019) - Ryan, Gerard Edward; Nicholson, Emily; Eames, Jonathan C.; Gray, Thomas N. E.; Loveridge, Robin; Mahood, Simon P.; Sum, Phearun; McCarthy, Michael A.
Abstract: We developed a method to estimate population abundance from simultaneous counts of unmarked individuals over multiple sites. We considered that at each sampling occasion, individuals in a population could be detected at 1 of the survey sites or remain undetected and used either multinomial or binomial simultaneous‐count models to estimate abundance, the latter being equivalent to an N‐mixture model with one site. We tested model performance with simulations over a range of detection probabilities, population sizes, growth rates, number of years, sampling occasions, and sites. We then applied our method to 3 critically endangered vulture species in Cambodia to demonstrate the real‐world applicability of the model and to provide the first abundance estimates for these species in Cambodia. Our new approach works best when existing methods are expected to perform poorly (i.e., few sites and large variation in abundance among sites) and if individuals may move among sites between sampling occasions. The approach performed better when there were >8 sampling occasions and net probability of detection was high (>0.5). We believe our approach will be useful in particular for simultaneous surveys at aggregation sites, such as roosts. The method complements existing approaches for estimating abundance of unmarked individuals and is the first method designed specifically for simultaneous counts. Abstract : Article impact statement : multinomial and binomial simultaneous‐count models estimate abundance of unmarked individuals in multiple sites. Abstract : Modelos de Conteo Simultáneo para Estimar la Abundancia a partir de Conteos de Individuos No Marcados con Detección Imperfecta Resumen: Desarrollamos un método para estimar la abundancia poblacional a partir de conteos simultáneos de individuos sin marcaje en múltiples sitios. Consideramos que en cada ocasión de muestreo los individuos de una población podrían ser detectados en uno de los sitios de censos o podrían permanecer sin ser detectados y usamos modelos de conteo simultáneo multinomial o binomial para estimar la abundancia, con el binomial como equivalente a un modelo de mezcla N con un solo sitio. Probamos el desempeño del modelo con simulaciones en un rango de probabilidades de detección, tamaños poblacionales, tasas de crecimiento, número de años, ocasiones de muestreo, y sitios. Después aplicamos nuestro método a tres especies de buitre que se encuentran en peligro crítico en Camboya para demostrar cuán aplicable es el modelo en el mundo real y para proporcionar las primeras estimaciones de abundancia para estas especies en Camboya. Nuestra nueva estrategia trabaja de mejor manera cuando se espera que los modelos existentes tengan un desempeño pobre (es decir, pocos sitios y una gran variación en la abundancia entre sitios) y si los individuos podrían moverse de un sitio a otro entre cada ocasión de muestreo. La estrategia tuvo un mejor desempeñó cuando hubo >8 ocasiones de muestreo y la probabilidad neta de detección fue alta (>0.5). Creemos que nuestra estrategia será especialmente útil para censos simultáneos en sitios de agregación, como los nidos. El método complementa las estrategias existentes para estimar la abundancia de individuos sin marcaje y es el primer método diseñado específicamente para conteos simultáneos. 摘要: 我们开发了一种利用多个位点未标记个体的同时计数来估计种群丰度的方法。我们认为每次抽样时种群中的个体要么出现在其中一个调查位点, 要么没有被发现, 因此可以用多项或二项同时计数模型来估计种群丰度, 而后者相当于一个位点的N混合模型。我们对检测概率、种群大小、增长率、年数、抽样情况和位点进行了一系列模拟, 测试了模型的性能。接下来我们将这个方法应用于柬埔寨的三种极度濒危的秃鹫, 以证明模型实用性, 这也是首次对柬埔寨的这些物种进行丰度估计。当现有方法不适用 (如只有少量位点或位点间丰度差异很大), 或是几次抽样之间动物的位置发生移动的情况下, 我们的新方法最为有效。抽样次数大于八次时, 我们的模型表现得更好, 其净检测概率较高 (>0.5) 。我们相信这一方法在对聚集位点 (如鸟群栖息处) 进行同时调查时尤其适用。它是对现有的未标记个体丰度估计方法的补充, 也是第一个专为同时计数调查而设计的方法。翻译: 胡怡思; 审校: 聂永刚